MODULATION CHARACTERISTICS OF A TUNABLE MULTISECTION DBR LASER - LEE, S; LEE, SY; PARK, HL; CHOI, WJ; LEE, JI; KANG, KN (KOREAN PHYSICAL SOC, 1993)
The first theoretical study of the modulation characteristics in a tunable multisection distributed Bragg reflector (DBR) laser, when the lasing wavelength changes continuously, is presented. Taking into account both the possibility of the laser operation away from the gain maximum and the nonlinear gain compression effect, we analyze the small-signal frequency and the intensity modulation (FM/IM) characteristics. It is found that the FM efficiency decreases and that the modulation bandwidth increases with increasing bias current to the passive section(s). The resonance peak and the phase shift decrease as the effect of nonlinear gain compression increases. These characteristics are not affected by changing the lasing wavelength continuously.
Keywords: SEMICONDUCTOR-LASERS; FREQUENCY; SINGLE; PHASE; GAIN